Analisis Penerapan GMP (Good Manufacturing Practices) Pada Produk Fresh Fillet Goldband Snapper (Pristimoides multidens) Skin-On di PT. Matsyaraja Arnawa Stambhapura Kupang, Nusa Tenggara Timur - Rahardian, Mydan Amlang; Suseno, Suseno; Lailatussifa, Rr. Radipta; Nugraha, Breva Rizqi Dyah (Innovative: Journal Of Social Science Research, 2025)
Indonesia is a maritime country located in a vast sea area, has many islands, surrounded by sea and water areas. Indonesian waters hold a lot of potential resource wealth that has not been explored and exploited optimally. Snapper fish resources are natural resources contained in water and therefore should be controlled, managed, and utilized as well as possible by the state in order to bring optimal and sustainable benefits. This study aims to analyze the implementation of GMP (Good Manufacturing Practices) in the production process of Fresh Fillet Goldband Snapper (Pristimoides multidens) Skin-On has been implemented properly or not implemented properly. The research was conducted at PT. Matsyaraja Arnawa Stambhapura, Kupang, East Nusa Tenggara and was carried out from February 24 to May 9, 2025. The research method used a survey method with an internship pattern. By using this method, the author can directly implement how the implementation of GMP has been implemented during the process. As a result, the implementation of GMP has been carried out properly, but there are shortcomings where during the process there was no metal detecting. The author suggests holding metal detecting activities in order to meet product safety.